Drug Interactions of Metformin Involving Drug Transporter Proteins - Naina Mohamed Pakkir Maideen; Abdurazak Jumale; Rajkapoor Balasubramaniam (Tabriz University of Medical Sciences, 2017)
Metformin is a most widely used medication all around the world to treat Type 2 diabetes mellitus. It is also found to be effective against various conditions including, Prediabetes, Gestational diabetes mellitus (GDM), Polycystic Ovarian Syndrome (PCOS), Obesity, Cancer, etc. It is a cationic drug and it depends Organic Cation Transporters (OCTs) and Multidrug and Toxin Extruders (MATEs) mostly for its pharmacokinetics movement. The probability of drug interaction increases with the number of concomitant medications. This article focuses the drug interactions of metformin and most of them are linked to the inhibition of OCTs and MATEs leading to increased plasma metformin concentrations and subsequent elevation of risk of Metformin Associated Lactic Acidosis (MALA). By identifying the drugs inhibiting OCTs and MATEs, the healthcare professionals can predict the drug interactions of metformin.